Assessment of Exposure to Noise of Workers to a Reinforcing Bar Rod Mill ArcelorMittal Algeria - MEDDEB, Wahiba; TADJINE, Kamel (Archives of Acoustics, 2016)
This work is a contribution to a normative approach of noise assessment in the professional environment. It permits the identification of the affected workstations on the one hand and on the other hand it constitutes an important support to the preoccupations of the impact study on the environment in plants. It also informs us on the adequate preparation of the procedures required by the Environmental Management System (ISO 14001) being implemented in steel-making complex ArcelorMittal Algeria. It constitutes an answer to the recommended environmental politics.The proposed calculation methods are verified according to the recognized sources (ISO 9612, 2009) and the results will be estimated in relation to the legal thresholds recommended by international bodies. The methodology for measuring the noise exposure levels has been done according to the following steps: work analysis; selection of measurement strategy; measurements; error handling and uncertainty evaluations; calculations; and presentation of results. This will lead us to an implementation of a corrective and preventive action plan intended to master this occupational risk carrying prejudice to the health of the workers.